Spain [stet] accession to the EMU: a long and hilly road - Balmaseda, Manuel; Sebastian, Miguel; Tello, Petry (Economic & Social Studies, 2002)
Europe has been the driving force of economic policy in Spain over the last four decades and the key factor behind the modernisation and globalisation of the Spanish Economy. Being a founding member of the Economic and Monetary Union (EMU) marked the achievement of one of the key goals in the process of European integration. This process was carried out in several stages. First, trade openness, which was bolstered by Spanish accession to the EEC in 1986 and the single market in 1992, and foreign direct investment abroad and portfolio investment, which grew exponentially in the run-up to Euro membership. Second, the process of nominal convergence, which allowed a more stable macroeconomic framework. Lower inflation and fiscal consolidation have resulted in higher sustainable growth. However, the process of real integration could have been even more successful. Spain?s income per capita still lies at 84 per cent of the European average. The slow pace of reform, in particular in the labour market, with high labour costs leading to persistent unemployment, and an inappropriate policy-mix in the late 1980s prevented Spain from reaping the full benefits of integration and of EMU. Achieving real convergence is the key challenge facing the Spanish economy in the future and Europe will remain a focal point in this venture.
Keywords: European Monetary Union; Economic policy; Spain; Europe